Pengaruh Kompensasi Dan Stres Kerja Terhadap Prestasi Kerja Karyawan Pada PT. Federal International Finance Pos Tandes Surabaya - Mujiani Mujiani; Hesti Pandu Widodo; Aridha Prassetya (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to determine whether there is an influence between compensation and work stress on employee work performance at PT. Federal International Finance, Pos Tandes Surabaya branch. The population and sample used as subjects in this study were 37 employees of PT. Federal International Finance, Pos Tandes Surabaya branch. The results of the analysis using multiple linear regression assisted by SPSS 18 statistical calculation software showed that there is an influence between compensation and work stress on employee work performance. Employee work performance will increase if compensation is increased and work stress is reduced. The author's suggestion is that companies continue to pay attention to compensation and work stress so that employee work performance can always increase and company goals can be achieved.